HUBUNGAN INTENSITAS KEBISINGAN TERHADAP GANGGUAN PENDENGARAN AKIBAT BISING (NIHL) PADA PEKERJA BAGIAN PRODUKSI PT X BATAM - Elvita Nora Susana; Nopri Esmiralda; Kemas Muhammad Zaki (Universitas Batam, 2026)
ABSTRACT Background: Noise Induced Hearing Loss (NIHL) is a hearing impairment due to continuous or certain duration of noise exposure. This hearing impairment usually develops slowly over several years, this hearing impairment can occur due to several factors such as noise intensity that exceeds the threshold value, age and also length of service. This study aims to analyze the relationship between noise intensity and noise-induced hearing impairment (NIHL) in production workers at PT X. Methods: This study is an observational analytical study with a cross-sectional approach. The study sample consisted of 67 workers in the production department of PT X. Data were obtained through workers' medical records and analyzed using the Chi-square test with a significance level of 95% (p ≤ 0.05). Results: Of the total 67 respondents, 35.8% were exposed to noise with an intensity of <85 dB and 64.2% were exposed to noise with an intensity of >85 dB. As many as 46.3% of workers did not experience noise-induced hearing loss (NIHL), and 53.7% of workers experienced noise-induced hearing loss (NIHL). Bivariate analysis showed a significant relationship between noise intensity and noise-induced hearing loss (NIHL) (p = 0.001). Conclusion: There is a significant relationship between noise intensity and noise-induced hearing loss (NIHL). Therefore, close monitoring and education regarding NIHL risk factors need to be improved to reduce the incidence and complications caused. Keywords: Noise Intensity, Hearing Loss, NIHL